STUDY ON EFFECT OF DIFFERENT PACKAGING MATERIALS AND SHELF LIFE ON THE PHYSICAL QUALITY OF CROSSBREED LANDRACE PORK - I K. A., Sucita; Sriyani, N L. P; Sumardani, N. L. G. (Jurnal Peternakan Tropika, 2021)
This research was aimed at determining the effect of wrapping material in shelf life and physical quality of  crossbreed Landrace pork. The  research was based on a 2 x 3 factorial design in a completely randomized design (CRD) of  2  levels  of  wrapping materials and 3 levels of storage period. ). The treatment of wrapping materials is plastic and teak leaves. The storage period treatment is wrapped in pork and stored at 4 hours (T4), 8 hours (T8) and 12 hours (T12). The data were analyzed using variance analysis (ANOVA) and the treatment that had a significant effect was further analysis using Duncan's multiple distance test. The results showed that there was no interaction between the wrapping material and the length of storage to the physical quality of the crossbreed Landrace pork. The difference in wrapping material has a noticeable effect (P<0.05) on the color of the meat while the difference in storage time has a noticeable effect (P<0.05) on the pH value of the meat. The conclusion of this study is that there is no interaction between the difference factor of wrapping material and the storage time to the physical quality of crossbreed Landrace pork. The storage time factor affects the meat pH variable, while the wrapping material factor affects the color variable of crossbreed Landrace pork. The length of storage in plastic-wrapped Landrace pork provides lower physical quality compared to teak leaves, judging by the variable pH and color of the meat. Keyword : pork, wrapping material, shelf life.